Efficacy and safety of transarterial chemoembolization combined with lenvatinib and camrelizumab in patients with BCLC-defined stage C hepatocellular carcinoma - Wu, Juan; Zeng, Jia; Wang, Huiwen; Huo, Zhuoni; Hou, Xunbo; He, Dongfeng (Frontiers in Oncology, 2023)
Objective: To investigate the effectiveness and safety of combining transarterial chemoembolization (TACE) with lenvatinib and camrelizumab in patients with Barcelona Clinic Liver Cancer (BCLC) stage C hepatocellular carcinoma (HCC). Methods: We retrospectively analyzed 141 patients with BCLC stage C HCC: 57 were treated with TACE combined with lenvatinib plus camrelizumab (T + L + C), 41 were treated with TACE combined with camrelizumab (T + C), and 43 were treated with TACE (TACE). The primary outcomes were overall survival (OS) and progression-free survival (PFS), and the secondary outcomes were the objective response rate (ORR) and adverse events (AEs). Factors that affected survival were identified via Cox regression analysis. Results: Comparison of the three groups revealed a significant difference in the median overall survival (mOS), 19.8 months (95% CI 15.7–23.9) in the T + L + C combined group vs 15.7 (95% CI 13.1–18.3) months in the T + C combined group vs 9.4 (95% CI 6.2–12.5) months in the TACE group (P < 0.001). The median progression-free survival (mPFS) was significantly better in the T + L + C combination group than in the T + C combination group and the TACE group [11.4 (95% CI 7.6–15.3) months vs 8.4 (95% CI 6.2–10.5) months vs 4.8 (95% CI 3.2–6.3) months, respectively, P < 0.001)]. The objective response rate (ORR) (57.9%) and the disease control rate (DCR) (75.4%) patients in the combined T + L + C group were higher than those in the other two groups. More patients in the combined T + L + C group experienced AEs, with 16 (28.1%) patients experiencing AEs of grade 3 or higher. Conclusions: In patients with BCLC stage C HCC, those receiving the T + L + C combination demonstrated a superior survival benefit and acceptable safety profile compared patients receiving either TACE or the T + C combination.